The Critical Discourse Analysis of Maudy Ayunda’s Speech at Press Conference on the Introduction of the Government Spokesperson for Indonesia's G20 Presidency - Dewa Ayu Made Juli Astari; Ni Nyoman Padmadewi; Ni Luh Putu Eka Sulistia Dewi (Linguistic, English Education and Art (LEEA) Journal, 2022)
This study aims to describe the transcript of Maudy Ayunda’s speech as a critical discourse analysis taken from a video from Youtube Chanel Liputan 6. Maudy Ayunda is a spokesperson for G20 Presidency in Indonesia. The method used by the researcher was qualitative descriptive with textual content analysis based on Van Dijk’s design. This analysis is divided into four parts: macro-structure, superstructure, superstructure, and microstructure. This study also examines the linguistic aspect. In the macro-structure, the textual content is analyzed thematically. The theme of Maudy Ayunda’s speech was about persuading Indonesian people to participate in making success the G20 Presidency in Indonesia. Then, for the superstructure, the text of Maudy Ayunda’s speech is divided into three main elements, namely: opening, content, and closing. In superstructure analyze the general meaning by providing supporting reasons organized in the opening, content, and closing of the discourse. In micro-structure analyzes semantically, which refers to the social meaning of the text and the persuasive language used in the text. Besides that, Maudy Ayunda used formal language when delivered her speech. Keywords: Critical Discourse Analysis, Speech, Van Djik